Re-Creation in Canadian First Nations Literatures: "When You Sing It Now, Just like New" - Ridington, Robin (Anthropologica, 2022)
Canadian First Nations literatures include both traditional oral performative genres and written texts. This paper reviews First Nations poetics as represented in oratory, fictional literature, presentations to Canadian courts and the visual arts. It concludes that contemporary expressive forms recreate those embedded in oral tradition. The paper cites examples from both oral and written sources. It concludes that a First Nations narrative technology continues to energize contemporary literary and expressive genres.